Simulation and optimisation for production of biogas from palm oil mill effluent (POME) using aspen plus - Tristan Law, Lee Kien; Dahawi, Yahya Ayesh; Siti Noredyani, Abdul Rahman; Abdul Halim, Abdul Razik (UTP Press, 2021)
POME undergoes anaerobic digestion to produce biogas, and when it is purifed, the biomass can be used as a fuel. This work aims to create a model to simulate the production of biogas and identify the key parameters of the water scrubber using Aspen Plus. The production of biogas was successfully simulated with a relative diference of less than 5%. The key parameters of scrubber in order of percentage contribution to the purity of biogas is as follows, the temperature of water (38.34%), column pressure (35.29%), water fow rate (23.75%) and lastly, number of stages (2.62%). By employing the optimum values, biogas with 99.3% methane purity was obtained.